Are predatory journals contaminating science? An analysis on the Cabells' Predatory Report - AKÇA, SÜMEYYE (ELSEVIER SCIENCE INC, 2021)
Predatory journals, which are a major concern of the academic community, generally do not properly fulfill the reviewing and editorial processes which are the most important pillars of scientific communication. In line with the principle of the accumulation of science, the papers that have not been faithfully reviewed in these journals cause a bad effect on the scholarly communication. In this study, the impact of 17 journals with addresses in Turkey in Cabells' Predatory Report (formerly Cabells' Journal Blacklist) to the literature were examined. For this purpose, the journal and article level descriptive statistics were examined for the aforementioned journals, and analyses were made for the citations from the papers published in the journals indexed in the Web of Science citation database. A total of 3427 papers were published in these journals, which started to be published between 2010 and 2015, and 389 citations were made to these papers from the journals listed in the WoS. Such highest citations come from Turkey (24.16%), then China (7.20%) addressed papers. In addition, although there are no papers in fields such as art, humanities and physics, it has been seen that there are citations to papers from these fields. This is important in terms of showing the widespread impact of science. A paper published without serious peer review in any predatory journal affects all fields of science in terms of its method, findings and discussions. Therefore, to reduce the misleading or false effect of predatory journals on the literature, a more skeptical behavior should be displayed about citing the papers published in these journals.
Keywords: Predatory journals; Citation analysis; Cabells' predatory report; PUBLISHERS; SIDE; RISE